Hubungan Panjang-Berat, Nisbah Kelamin, dan Indeks Kematangan Gonad Kerang Darah (Anadara granosa LINN. 1758) di Perairan Muara Gembong â Bekasi - dody, safar; mumpuni, fia sri; madi, wahid (Universitas Djuanda Bogor, 2018)
This research was conducted in the waters ofÂ Muara Gembong, Bekasi, on Â January to March, 2018. Sampling of blood cockle is carried out in 3 station vertically to the direction of the sea. Determination of station is carried out based onÂ the fishing ground of the fisherman. Analyses of blood cockle is carried out in the Laboratory of the Research Center for Oceanography, LIPI, Ancol â North Jakarta. This research was aimed to analyze the reproductive biological aspectsÂ which includes the ratio of gender, the gonad maturity rate, the gonad maturity index, the length-weight relationship, the condition factor of Anadara granosa in the waters of Muara Gembong, Bekasi. The results of observation of 400 samples showed that the length-weight relationship of blood cockle ofÂ female andÂ maleÂ has the pattern of the negativeÂ allometric relationship. The overall ratio of gender between the blood cockle of male and female is 1.3:1. The average value of the gonad maturity index of the male blood cockle is 1.1874 and theÂ value of the gonad maturity index of the female blood cockle is 1.1983.Â Key words: Anadara granosa, growth, the ratio of gender, gonad maturity index